2013
DOI: 10.1080/03670244.2012.706131
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Beverages Derived from Wild Food Plant Species in the Vhembe District, Limpopo Province in South Africa

Abstract: Beverages derived from wild plant species play an important role in local and traditional food systems in rural communities such as in the Vhembe District, South Africa. Conducting research on such foodstuffs may help to prevent loss of indigenous knowledge on potential dietary sources for needy households. Through surveys and focussed group discussions, 41 different beverage-making plant species were identified. Traditional beverage making processes are of three types. Preparing teas involve a boiling process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…Respondents indicated the storage treatment and estimated the storage time of the fruit based on their experience. They indicated that picking of mature unripe fruits for storage in burial places also reduces competition from other fruit collectors, especially of a wellknown, sweet tasting variety, which is in line with findings of Motlhanka et al (2008) and Rampedi and Olivier (2013). Unripe mature fruits can be stored in this manner for more than two months (according to 18% of the respondents).…”
Section: Fruit Storage Practices and Constraintssupporting
confidence: 56%
See 1 more Smart Citation
“…Respondents indicated the storage treatment and estimated the storage time of the fruit based on their experience. They indicated that picking of mature unripe fruits for storage in burial places also reduces competition from other fruit collectors, especially of a wellknown, sweet tasting variety, which is in line with findings of Motlhanka et al (2008) and Rampedi and Olivier (2013). Unripe mature fruits can be stored in this manner for more than two months (according to 18% of the respondents).…”
Section: Fruit Storage Practices and Constraintssupporting
confidence: 56%
“…Data collection for fruits of the same species may be imprecise (Termote et al 2010). BUnder-differentiation^of a species is encountered when a single vernacular name can be used for species of morphological similarity, or Bover-differentiation^when several names are used for one species (Rampedi and Olivier 2013). Thus, to gather reliable and reproducible information, the species were grouped into two major groups: group A (comprising S. cocculoides and S. spinosa) and group B (S. innocua and S. madagascariensis).…”
Section: Resultsmentioning
confidence: 99%
“…When fully developed though unripe fruits are harvested, they are subsequently buried under a thin layer of sand for several months until ripe (or until they liquefy) to protect them from other fruit hunters and animals (2,11,24,51) and to prevent postharvest losses (Fig. 1).…”
Section: Post-harvest Handling and Storagementioning
confidence: 99%
“…Reduction of post-harvest losses and increase in shelf life have become urgent needs to promote better use of monkey oranges. To prolong shelf life and maintain quality, the fruit is sometimes domestically processed to jams, juices, wine, beer, fritters, muffins or dried fruit leathers, (9)(10)(11)(12)(13) but still most of the product is lost if not consumed fresh.…”
mentioning
confidence: 99%
“…Reduction of post-harvest losses and increase in shelf life have become an urgent need to promote better use of monkey oranges. To prolong shelf life and maintain quality, the fruit is sometimes domestically processed to jams, juices, wine, beer, fritters, muffins or dried fruit leathers McGregor, 1995;Orwa et al, 2009;Rampedi & Olivier, 2013;Zinyama et al, 1990), but still most of the product is lost if not consumed fresh.…”
Section: Introductionmentioning
confidence: 99%